PENGARUH PROFITABILITAS, LEVERAGE DAN PERTUMBUHAN LABA TERHADAP NILAI PERUSAHAAN (STUDY PADA PERUSAHAAN RETAIL TAHUN 2021-2023) - Habibur Rohman, Mohammad; Rodhiyah, Ma’rufatur; Dedyansyah, Achmad Farid; Mahmudah, Annita (Jurnal Bina Bangsa Ekonomika, 2025)
This study aims to examine the effect of profitability, leverage, and profit growth on company value in retail sector companies listed on the Indonesia Stock Exchange for the period 2021-2023. The study uses a quantitative approach with multiple linear regression methods. The results of the study indicate that profitability does not have a significant effect on company value, leverage has a significant positive effect, while profit growth has a significant negative effect. These findings indicate that a good leverage policy can increase company value, while ineffective profit growth can decrease company value. The implication of the study is the need for companies to manage their financial structure carefully to maximize company value.